2017
DOI: 10.1177/0954411917703676
|View full text |Cite
|
Sign up to set email alerts
|

TTK Chitra tilting disc heart valve model TC2: An assessment of fatigue life and durability

Abstract: Average age group of heart valve replacement in India and most of the Third World countries is below 30 years. Hence, the valve for such patients need to be designed to have a service life of 50 years or more which corresponds to 2000 million cycles of operation. The purpose of this study was to assess the structural performance of the TTK Chitra tilting disc heart valve model TC2 and thereby address its durability. The TC2 model tilting disc heart valves were assessed to evaluate the risks connected with pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…A critical step in translation of decellularised heart valve roots for use as replacement heart valves, is to have better understanding of in vitro durability and failure mechanisms due to the impact of cyclic physiological loading. Many studies [24,26,27,[43][44][45][46][47][48] have reported the fatigue and durability of replacement heart valves under accelerated cyclic loading conditions. The fatigue of conventional mechanical and bioprosthetic (glutaraldehyde fixed) replacement heart valves have been evaluated using the accelerated fatigue assessment method and showed similar fatigue in comparison to the fatigue of retrieved in vivo heart valves [47,48].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A critical step in translation of decellularised heart valve roots for use as replacement heart valves, is to have better understanding of in vitro durability and failure mechanisms due to the impact of cyclic physiological loading. Many studies [24,26,27,[43][44][45][46][47][48] have reported the fatigue and durability of replacement heart valves under accelerated cyclic loading conditions. The fatigue of conventional mechanical and bioprosthetic (glutaraldehyde fixed) replacement heart valves have been evaluated using the accelerated fatigue assessment method and showed similar fatigue in comparison to the fatigue of retrieved in vivo heart valves [47,48].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies [24,26,27,[43][44][45][46][47][48] have reported the fatigue and durability of replacement heart valves under accelerated cyclic loading conditions. The fatigue of conventional mechanical and bioprosthetic (glutaraldehyde fixed) replacement heart valves have been evaluated using the accelerated fatigue assessment method and showed similar fatigue in comparison to the fatigue of retrieved in vivo heart valves [47,48]. However, for heart valves comprising of leaflets with a greater visco-elastic response, such as polymer materials and (non-glutaraldehyde fixed) biological tissue the fatigue mechanism was not predictive of in vivo wear mechanisms [24][25][26].…”
Section: Discussionmentioning
confidence: 99%